'Authenticity' as Intermediary: Contested Memories of the Mughal Fort of Old Delhi. (1st March 2018) - Waraich, Saleema
This article traces the contested symbolic values of the Red Fort (Lal Qila) of Delhi. Specifically, it queries the ways in which politically bound memories of the site negotiated a Mughal-Muslim past and constructions of a national identity in the 1990s and 2000s. As examined here, these negotiations were made manifest in conservation practices at the site, the criticisms and debates that ensued, and competing claims over what constitutes an 'authentic' representation of the site, thus speaking to a collision of attitudes and approaches to conserving India's Mughal heritage and envisaging India's ambitions and identity.